2007
DOI: 10.1097/gco.0b013e3280e129ba
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary oestrogens on male and female fertility

Abstract: Phytoestrogens are still a current research topic in reproduction and fertility. Genistein is a putative therapeutic tool in cancer treatment although this must be considered along with evidence that it may cause DNA damage in sperm, depending on the concentration. The effects of phytoestrogen in the body are not limited to oestrogenic action. Much more epidemiological data are required to interpret current molecular studies, and those of previous years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Indeed, it was demonstrated that isoflavones adversely affect the reproductive organ development and cause bleeding in male animals [ 12 13 ] . Chavarro et al explained that ingestion of soybean foods renders the isoflavones to interrupt the activity of body hormones stimulating spermatogenesis, leading to a decrease in sperm number [ 14 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was demonstrated that isoflavones adversely affect the reproductive organ development and cause bleeding in male animals [ 12 13 ] . Chavarro et al explained that ingestion of soybean foods renders the isoflavones to interrupt the activity of body hormones stimulating spermatogenesis, leading to a decrease in sperm number [ 14 ] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the effect on the hypothalamic-pituitary-testosterone axis has been shown to cause compensated hypogonadism [67]. Also, the effect on fertility in males of reproductive age is a rising concern [83]. Kumar et al [84] did a 12 week randomized, interventional study with daily supplementation of 80 mg of oral purified isoflavone/day versus placebo in men with early prostate cancer (n=53), and reported no clinical toxicity from the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Des investigations approfondies sur la responsabilité de ces perturbations endocriniennes quant à la baisse de la production spermatique ou de malformations congénitales sont actuellement en cours d'analyse (Bhatia, 2005) et de nombreuses expérimentations in vivo et in vitro démontrent effectivement que certains produits chimiques rejetés dans l'environnement ont des effets délétères sur la reproduction (Jobling & Tyler, 2006 ;Longnecker et al, 2003). Parmi les agents susceptibles d'induire des effets nocifs sur la fonction reproductive, on peut citer les produits d'origine anthropique, comme les glycoéthers (Multigner et al, 2005), les pesticides organochlorés (Oliva et al, 2001), et ceux d'origine naturelle comme les phyto-oestrogènes ou les produits de combustion (West, 2007). Cependant, le manque de connaissance sur les voies de signalisation de ces perturbations, les niveaux d'expositions des espèces et les risques encourus suscitent un intense effort de recherche de la part de la communauté scientifique pour élucider les mécanismes à l'origine de ses dysfonctions.…”
unclassified